THA With Delta Ceramic on Ceramic: Results of a Multicenter Investigational Device Exemption Trial - Hamilton, William G. (Springer-Verlag, 2009)
Although the published studies on the outcomes of total hip arthroplasty (THA) performed with currently available ceramic components show high survivorship and low bearing wear at midterm followup, concern over ceramic fracture and squeaking persist. For these reasons, the use of ceramic is limited. Recently, a new alumina matrix composite material (Delta ceramic) with improved material properties was developed to address these concerns. We report the early outcomes and complications of a prospective, randomized, multicenter trial of 263 patients (264 hips) at eight centers, comparing a Delta ceramic-on-ceramic (COC) articulation with a Delta ceramic head-crosslinked polyethylene bearing combination (COP). There were 177 COC hips and 87 COP hips. Complications were reported for all patients, whereas clinical and radiographic results were provided for the 233 patients with minimum 2-year followup (average, 31.2 months; range, 21–49 months). The Harris hip scores and clinical, radiographic, and survivorship outcomes were similar in both groups. There were four (2%) revisions in the COC group and two (2%) in the COP group. We encountered three intraoperative ceramic liner-related events. In addition, one patient receiving the COC underwent revision for chipping of the ceramic liner, and a second had ceramic fragmentation on followup radiographs but has not undergone revision. These liner related complications remain a concern. No patient reported squeaking in either group; this leaves us hopeful the new material will lessen the frequency of squeaking. In the short term, the Delta COC articulation provided similar functional scores and survivorship and complication rates with the ceramic head mated with crosslinked polyethylene. Level of Evidence: Level I, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.